Reduced serum cholinesterase is an independent risk factor for all-cause mortality in the pediatric intensive care unit - Yue, Chaoyan; Zhang, Chunyi; Ying, Chunmei; Jiang, Hua (Frontiers in Nutrition, 2022)
Abstract Objective：Our aim was to assess the relationship between serum cholinesterase levels at intensive care unit admission and all-cause mortality in the pediatric intensive care unit. Methods: We used the pediatric intensive care unit database (a large pediatric intensive care database in China from 2010 to 2018) to conduct a retrospective analysis to evaluate the serum cholinesterase levels at intensive care unit admission of 11751critically ill children enrolled to the intensive care unit. We analyzed the association between serum cholinesterase and all-cause mortality. Adjusted smoothing spline plots, subgroup analysis and segmented multivariate logistic regression analysis were conducted to estimate the relative risk between proportional risk between serum cholinesterase and death. Results: Of the 11751 children, 703 (5.98%) died in hospital. After adjusting for confounders, there was a negative association between serum cholinesterase and the risk of death in pediatric intensive care unit. For every 1000 U/L increase in serum cholinesterase, the risk of death was reduced by 16 % (adjusted OR = 0.84, 95% CI: 0.79, 0.89). The results of sensitivity analysis showed that in different stratified analyses (age, intensive care unit category, albumin, alanine aminotransferase, creatinine, neutrophils), the effect of serum cholinesterase on all-cause mortality remained stable. Conclusion: After adjusting for inflammation, nutrition, and liver function factors, cholinesterase reduction is still an independent risk factor for pediatric intensive care unit all-cause mortality.